2005
DOI: 10.1007/bf02977408
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of microemulsion systems for transdermal delivery of aceclofenac

Abstract: An ONW microemulsion system was developed to enhance the skin permeability of aceclofenac. Of the oils studied, Labrafil M 1944 CS was chosen as the oil phase of the microemulson, as it showed a good solubilizing capacity. Pseudo-ternary phase diagrams were constructed to obtain the concentration range of oil, surfactant, Cremophor ELP, and co-surfactant, ethanol, for micoemulsion formation. Eight different formulations with various values of oil of 6-30%, water of 0-80%, and the mixture of surfactant and co-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 12 publications
1
38
1
3
Order By: Relevance
“…The peak point in the viscosity-water content profile is denoted as the transition point of W/O to O/W microemulsion [15,16]. In this study, the peak points were only found in microemulsion systems using high HLB surfactants (i.e., Tween 20® and Labrasol®) but not in the ones using low HLB surfactants (i.e., Span 20®).…”
Section: Characterization Of the Selected Microemulsionsmentioning
confidence: 65%
“…The peak point in the viscosity-water content profile is denoted as the transition point of W/O to O/W microemulsion [15,16]. In this study, the peak points were only found in microemulsion systems using high HLB surfactants (i.e., Tween 20® and Labrasol®) but not in the ones using low HLB surfactants (i.e., Span 20®).…”
Section: Characterization Of the Selected Microemulsionsmentioning
confidence: 65%
“…Similar solution was successfully applied to monitor the skin delivery of steroidal drugs from microemulsions. 23) Other studies also employed 40% propylene glycol solution as the receptor solution.…”
Section: Methodsmentioning
confidence: 99%
“…A 0.05 level of significance (pϽ0.05) was considered significant. The skin flux can be experimentally determined from the following equation 23) :…”
Section: Methodsmentioning
confidence: 99%
“…Zeta potential and the dynamic light scattering (DLS) of the microemulsions were analysed in triplicate at 25 o C [13].…”
Section: Zeta-potential Measurementmentioning
confidence: 99%